Assessing stone walls habitat quality – Which factors affect bryophytes and macrolichens on farmland stone walls in Ireland?. (June 2022) - Ruas, Sara; Rotchés-Ribalta, Roser; Ó hUallacháin, Daire; Volpato, Alessio; Gormally, Michael; White, Blanaid; Moran, James
Highlights: Stone walls are ubiquitous features in European agricultural landscapes. Bryophytes and macrolichens can be used as proxies of stone wall habitat quality. Farm management variables and altitude relate to bryophytes and macrolichens in stone walls. Results, if confirmed, can guide actions for improving quality of stone walls. Abstract: Stone walls are ubiquitous field boundaries used to restrict livestock movement or to separate property. Bryophytes and lichens are often the dominant vegetation in dry stone walls and are strongly affected by local microhabitat characteristics. Bryophytes and lichens related metrics can be used to define habitat quality of stone walls. The current study assessed how richness and cover of bryophytes and macrolichens in dry stone walls related to each other and how different environmental variables and farm management descriptors determined richness and cover of both groups in dry stone walls. Bryophytes and macrolichens were sampled in stone walls on sixteen farms across a management intensity gradient in Ireland. Bryophyte cover correlated positively and significantly with bryophyte richness and macrolichen cover and richness, and can thus be used to assess stone walls quality. Farm management intensity emerged as the variable most strongly related with species richness of bryophytes and cover of both groups. Altitude also emerged as a strong predictor of both groups' richness and cover. This study provides a novel perspective on stone wall habitat quality and results indicate that by promoting extensive farming it is possible to increase stone walls quality.